2004
DOI: 10.1542/peds.113.1.e26
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Recall of Children With Chronic Medical Conditions for Influenza Vaccination

Abstract: ABSTRACT. Objectives. Despite long-standing recommendations to provide annual influenza vaccination to children with chronic medical conditions, immunization rates are <10% in most primary care settings. Many obstacles impede implementation of these recommendations, including the challenge of identifying targeted children and the need to immunize yearly in a short time interval. The objective of this study was to assess the accuracy of billing data for identifying children who have high-risk conditions (HRCs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
95
1
6

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 37 publications
3
95
1
6
Order By: Relevance
“…Previous studies have examined interventions to improve influenza vaccination in children, [10][11][12][13][14] but this study is the first, to our knowledge, to simultaneously assess practice and child characteristics and practice strategies associated with influenza vaccination coverage in geographically diverse sites. We found that two modifiable factors were associated with increased complete influenza vaccinations--any practice visit during October through January and evening/weekend influenza vaccine clinics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have examined interventions to improve influenza vaccination in children, [10][11][12][13][14] but this study is the first, to our knowledge, to simultaneously assess practice and child characteristics and practice strategies associated with influenza vaccination coverage in geographically diverse sites. We found that two modifiable factors were associated with increased complete influenza vaccinations--any practice visit during October through January and evening/weekend influenza vaccine clinics.…”
Section: Discussionmentioning
confidence: 99%
“…From this framework, we selected relevant factors from the literature and immunization strategies recommended by this Task Force. [10][11][12][13][14]19 The survey was pilot tested in a convenience sample of pediatric providers and their office managers. The self-administered survey included 22-items concentrating on practice patterns for administering vaccine to children aged 6-23 months.…”
Section: Practice Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Otros estudios en población de niños con enfermedades crónicas han mostrado que sólo 17 a 25% reciben vacuna antigripal 29 .…”
Section: Discussionunclassified
“…Para mejorar la adherencia a la vacunación en niños con NECMES se requiere incorporar registros computacionales 16,18,19 con acceso a información en forma confiable, expedita y transversal, entre centros de atención primaria y terciaria, que incluya, además, sistemas de recordatorio o aviso automáticos para los padres y encargados de vacunación [27][28][29] .…”
Section: Discussionunclassified